Extraordinary Large Giant Congenital Melanocytic Nevus Treated with Integra Dermal Regeneration Template - Tønseth, Kim A. (Plast Reconstr Surg Glob Open, 2015)
Garment-like giant congenital melanocytic nevi are very rare, and those being treated are most often offered excision and split-thickness skin transplantation. Due to the risk of restricted mobility secondary to shrinkage and hypertrophic scarring of the transplant, we treated to date the largest reported giant congenital melanocytic nevus (16% total body surface area) with Integra dermal regeneration template (Integra Life Sciences, Plainsboro, N.J.), giving a more functional skin reconstruction. In addition, the dermal regeneration template had to be covered with split-thickness skin transplant including multiple smaller nevi due to lack of larger area with normal skin.